2020
DOI: 10.1098/rstb.2019.0573
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics of the modern and historical human oral microbiome with phylogenetic studies onStreptococcus mutansandStreptococcus sobrinus

Abstract: We have recently developed bioinformatic tools to accurately assign metagenomic sequence reads to microbial taxa: SPARSE for probabilistic, taxonomic classification of sequence reads; EToKi for assembling and polishing genomes from short-read sequences; and GrapeTree, a graphic visualizer of genetic distances between large numbers of genomes. Together, these methods support comparative analyses of genomes from ancient skeletons and modern humans. Here, we illustrate these capabilities with 784 samples from his… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 68 publications
(117 reference statements)
0
22
0
Order By: Relevance
“…Considering that the perturbed microbial community of the dental plaque is the main reason behind the carious processes, the "core microbiome of caries" have been proposed in order to better understand the microbial community in the occurrence and development of caries [Kressirer et al, 2018;Kazemtabrizi et al, 2020]. Several highly acidogenic and acid-tolerant bacteria have been considered as "core microbiome" associated with caries, including Streptococcus mutans, Streptococcus sobrinus, and certain Lactobacillus, Bifidobacterium, and Scardovia [Saraithong et al, 2015;Neves et al, 2017;Achtman and Zhou, 2020]. When it comes to Streptococcus mutans, it was regarded as one of the major etiological agents of human dental caries with its capacity to orchestrate changes in the plaque microbiome via the extracellular polysaccharide matrix and acid production [Lemos et al, 2019].…”
Section: Resultsmentioning
confidence: 99%
“…Considering that the perturbed microbial community of the dental plaque is the main reason behind the carious processes, the "core microbiome of caries" have been proposed in order to better understand the microbial community in the occurrence and development of caries [Kressirer et al, 2018;Kazemtabrizi et al, 2020]. Several highly acidogenic and acid-tolerant bacteria have been considered as "core microbiome" associated with caries, including Streptococcus mutans, Streptococcus sobrinus, and certain Lactobacillus, Bifidobacterium, and Scardovia [Saraithong et al, 2015;Neves et al, 2017;Achtman and Zhou, 2020]. When it comes to Streptococcus mutans, it was regarded as one of the major etiological agents of human dental caries with its capacity to orchestrate changes in the plaque microbiome via the extracellular polysaccharide matrix and acid production [Lemos et al, 2019].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the expectation that such a major lifestyle change should result in a microbiome shift as detected in prior gut microbiome studies [24], Eisenhofer et al [23] observed that the microbiome variation changed little between these periods, with a noteworthy exception of Edo-period differences between the sexes, which they propose reflects traditional cultural practices. In the third article, Achtman & Zhou [25] discuss recently developed bioinformatic tools for investigating microbial diversity in metagenomic datasets, and they use these to examine the oral microbiome from ancient dental calculus in addition to modern saliva and dental calculus samples across a broad geographical region. In doing so, they cast doubt on the existence of the traditional oral complexes of bacteria, such as the red complex, defined by Socransky et al [26] and illustrate the importance of using new genomic methods to assess taxon diversity in the oral microbiome.…”
mentioning
confidence: 99%
“… Streptococcus mutans is a ubiquitous species of the oral microbiome of modern humans [9, 36, 37]. Besides its important role in cariogenesis, S.…”
Section: Discussionmentioning
confidence: 99%